2012
DOI: 10.1371/journal.pone.0029712
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo Hemorrhagic Fever Virus-Infected Hepatocytes Induce ER-Stress and Apoptosis Crosstalk

Abstract: Crimean-Congo hemorrhagic fever virus (CCHFV) is a widely distributed tick-borne member of the Nairovirus genus (Bunyaviridae) with a high mortality rate in humans. CCHFV induces a severe disease in infected patients that includes, among other symptoms, massive liver necrosis and failure. The interaction between liver cells and CCHFV is therefore important for understanding the pathogenesis of this disease. Here, we described the in vitro CCHFV-infection and -replication in the hepatocyte cell line, Huh7, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 67 publications
5
54
0
Order By: Relevance
“…These time points correlate with high levels of progeny virus production and release from the host cells. Apoptosis-inducing viruses of the family Bunyaviridae like Oropouche virus, Crimean-Congo hemorrhagic fever virus or hantavirus show comparable time-courses for the induction of apoptosis (Acrani et al, 2010;Karlberg et al, 2011), and for these viruses it was shown that apoptosis of the host cell was not induced by binding or entry of the virus but by viral replication (Acrani et al, 2010;Li et al, 2004;Rodrigues et al, 2012). Similarly, experiments with UV-inactivated viruses such as West Nile virus, Newcastle disease virus, Oropouche virus and enterovirus have also identified a dependence on viral replication as the major apoptosis-inducing factor (Acrani et al, 2010;Kleinschmidt et al, 2007;Ravindra et al, 2008;Shih et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These time points correlate with high levels of progeny virus production and release from the host cells. Apoptosis-inducing viruses of the family Bunyaviridae like Oropouche virus, Crimean-Congo hemorrhagic fever virus or hantavirus show comparable time-courses for the induction of apoptosis (Acrani et al, 2010;Karlberg et al, 2011), and for these viruses it was shown that apoptosis of the host cell was not induced by binding or entry of the virus but by viral replication (Acrani et al, 2010;Li et al, 2004;Rodrigues et al, 2012). Similarly, experiments with UV-inactivated viruses such as West Nile virus, Newcastle disease virus, Oropouche virus and enterovirus have also identified a dependence on viral replication as the major apoptosis-inducing factor (Acrani et al, 2010;Kleinschmidt et al, 2007;Ravindra et al, 2008;Shih et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For many viruses, like SeV, West Nile virus, Crimean-Congo hemorrhagic fever virus, simian varicella virus, transmissible gastroenteritis virus or human astrovirus, it has been demonstrated that infection of the host cell can lead to activation of both caspases 8 and 9 and their associated signal transduction pathways (Banos-Lara & Méndez, 2010;Bitzer et al, 1999Bitzer et al, , 2002Eleouet et al, 1998;Kleinschmidt et al, 2007;Pugazhenthi et al, 2009;Rodrigues et al, 2012). The exact mechanism(s) by which these signalling pathways are activated during TCRV infection, and which cellular factors are involved, remain to be analysed.…”
Section: Discussionmentioning
confidence: 99%
“…CCHFV replication in cell culture results in the induction of apoptosis at late time points within the infectious cycle (40), and the onset of apoptosis coincides with cleavage of the N protein by cellular caspase-3, at a conserved DEVD motif at residues 269 to 272 (19).…”
Section: ) (C)mentioning
confidence: 99%
“…PUMA-dependent induction of PCD is reported after bacterial and viral infections [65][66][67]. Recently, an increased expression of PUMA and NOXA has been described in gastric epithelial cells infected with Helicobacter pylori [65].…”
Section: Immune Modulation Infectionsmentioning
confidence: 99%